The Role of Carotenogenic Metabolic Flux in Carotenoid Accumulation and Chromoplast Differentiation: Lessons From the Melon Fruit - Feder, Ari; Chayut, Noam; Gur, Amit; Freiman, Zohar; Tzuri, Galil; Meir, Ayala; Saar, Uzi; Ohali, Shachar; Baumkoler, Fabian; Gal-On, Amit; Shnaider, Yula; Wolf, Dalia; et al. (Frontiers in Plant Science, 2019)
Carotenoids have various roles in plant physiology. Plant carotenoids are synthesized in plastids and are highly abundant in chromoplasts of ripening fleshy fruits. Considerable research effort has been devoted to elucidating mechanisms that regulate carotenoid biosynthesis, yet, little is known about the mechanism that triggers storage capacity, mainly through chromoplast differentiation. The Orange gene (OR) product stabilizes phytoene synthase protein (PSY) and triggers chromoplast differentiation. OR underlies carotenoid accumulation in orange cauliflower and melon. The OR's ‘golden SNP’, found in melon, alters the highly evolutionary conserved Arginine108 to Histidine and controls β-carotene accumulation in melon fruit, in a mechanism yet to be elucidated. We have recently shown that similar carotenogenic metabolic flux is active in non-orange and orange melon fruit. This flux, probably leads to carotenoid turnover, but known carotenoid turnover products are not detected in non-orange fruit. Arrest of this metabolic flux, using chemical inhibitors or mutations, induces carotenoid accumulation and biogenesis of chromoplasts, regardless of the allelic state of OR. We suggest that the ‘golden SNP’ induces β-carotene accumulation probably by negatively affecting the capacity to synthesize downstream compounds. The accumulation of carotenoids induces chromoplast biogenesis through a metabolite-induced mechanism. Carotenogenic turnover flux can occur in non-photosynthetic tissues, which do not accumulate carotenoids. Arrest of this flux by the 'golden SNP' or other flux-arrest mutations is a potential tool for the biofortification of agricultural products with carotenoids.